m^2-n^2/m^2-2mn+n^2 ,其中m^2+n^2-2m-6n+10=0
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 17:51:54
m^2-n^2/m^2-2mn+n^2,其中m^2+n^2-2m-6n+10=0m^2-n^2/m^2-2mn+n^2,其中m^2+n^2-2m-6n+10=0m^2-n^2/m^2-2mn+n^2,
m^2-n^2/m^2-2mn+n^2 ,其中m^2+n^2-2m-6n+10=0
m^2-n^2/m^2-2mn+n^2 ,其中m^2+n^2-2m-6n+10=0
m^2-n^2/m^2-2mn+n^2 ,其中m^2+n^2-2m-6n+10=0
(m²-2m+1)+(n²-6n+9)=0
(m-1)²+(n-3)²=0
所以m-1=n-3=0
m=1,n=3
所以原式=(m+n)(m-n)/(m-n)²
=(m+n)/(m-n)
=(1+3)/(1-3)
=-2
∵m^2+n^2-2m-6n+10=0
∴(m²-2m+1)+(n²-6n+9)=0
(m-1)²+(n-3)²=0
m-1=0,n-3=0
得m=1,n=3
m^2-n^2/m^2-2mn+n^2
=(m+n)(m-n)/(m-n)²
=(m+n)/(m-n)
=(1+3)/(1-3)
=-2
m^2+n^2-2m-6n+10=0
∴m²-2m+1+n²-6n+9=0
(m-1)²+(n-3)²=0
∴m-1=0
n-3=0
∴m=1
n=3
m^2-n^2/m^2-2mn+n^2
=(m+n)(m-n)/(m-n)²
=(m+n)/(m-n)
当m=1,n=3时
原式=(1+3)/(1-3)=-2
由m^2+n^2-2m-6n+10=0,得
(m-1)^2+(n-3)^2=0
所以m=1,n=3
带入m^2-n^2/m^2-2mn+n^2得
m^2-n^2/m^2-2mn+n^2=(m+n)/(m-n)=-2
mn(m-n)-m(n-m)²2m(m-n)(2n-m)求过程
因式分解: m(m-2n)+n(2mn-m^2)
mn(m-n)-m(n-m)2 2是平方
计算m/(m+n)+(mn)/(n^2 -m^2)
分解因式mn(m-n)-m(n-m)^2
m^+2n-mn-2m
一道初二计算题 m/(m-n)-n/(m+n)+2mn/(m^2-n^2)
(n/m-n)+(m/m+n)-2mn/n^2-m^2
m/m-n减n/m+n加2mn/m的平方-n的平方
化简:m/m -n 减 n/m+n 加 2mn/m平方减n平方
1/M+1/N=5 (3M+MN+2N) / (M-MN=3N)
化简(m²/m-n - m+n)÷2m²-mn/n - m
(5mn-2m+3n)+(-7m-7mn)
(5mn-2m+3n)+(-7m-7mn)
(2m+n)(4m^2-2mn+n^2)
m^3n-2m^2n^2+mn^3
[(m+n)^2-(m-n)^2]/(-2mn)
2m*m-n*n+mn怎么因式分解